Qualitative methods in implementation research: An introduction - Hamilton, Alison B.; Finley, Erin P. (Psychiatry research, 2019)
•Qualitative methods are critical to implementation research.•Qualitative methods address the hows and whys of implementation.•Interviews and observation are key methods in implementation research.•Data collection and analysis are typically driven by an implementation framework.•Rapid turn-around of qualitative findings supports implementation and evaluation. Qualitative methods are a valuable tool in implementation research because they help to answer complex questions such as how and why efforts to implement best practices may succeed or fail, and how patients and providers experience and make decisions in care. This article orients the novice implementation scientist to fundamentals of qualitative methods and their application in implementation research, describing: 1) implementation-related questions that can be addressed by qualitative methods; 2) qualitative methods commonly used in implementation research; 3) basic sampling and data collection procedures; and 4) recommended practices for data analysis and ensuring rigor. To illustrate qualitative methods decision-making, a case example is provided of a study examining implementation of a primary care-based collaborative care management model for women Veterans with anxiety, depression, and PTSD.